The Effectiveness of Using Smalltalk2me AI in Teaching Speaking Skills - Maulidianti, Irma; Berliana, Narisa; Yuliana, Yohanes Gatot Sutapa (Institut Agama Islam Negeri Ponorogo, 2024)
The purpose of this study is to find out the effectiveness of using Smalltalk2me AI in teaching speaking skills to secondary students. This quantitative research implemented a one-group pretest-posttest pre-experimental design. The collection of data process consisted of three steps: pre-test, treatment, and post-test. Then the researchers found the results of students’ achievement after they were taught by using Smalltalk2me AI. This research used Microsoft Excel to analyze the data by looking for the mean, standard deviation, T-test value, and T-test table. The findings of this study revealed that the average of the post-test was higher than the average of the pretest (30,75>41). It means that this study discovered a significant or substantial difference between the pre-test and post-test scores for students who had been taught by using Smalltalk2me AI. Therefore, it is possible to infer that Smalltalk2me AI is an excellent tool to teach speaking skills since tenth-grade students at SMA 1 Sajingan could be more active in speaking with high accuracy and great fluency.